Title must be Capitalized First Word and Maximum Two Lines Only Three Lines Not Acceptable - Handayani, Ika Fitri; Ngaliman, Ngaliman (Universitas Batam, 2022)
The purpose of this study was to determine how much influence competence, communication and work stress have on employee performance. Employee performance works as the dependent variable in this study, while competence, communication and work stress are variables that function as independent variables. This study uses 100 respondents who can be divided by gender and can be divided into two (2) groups, namely: male sex as many as 66 people (60%) and female sex as many as 34 people (34%). This study uses a quantitative approach with a questionnaire method. Data analysis used the Statistical Package for Social Sciences (SPSS) program. The results showed that there was a significant influence between competence and communication on the performance of employees of PT. Citra Shiyard's and the non-significant effect of work stress on employee performance at PT. Citra Shipyard. It can be said that the second variable has a strong influence on improving employee performance.